A 'New Arms Race'? Framing China and the U.S.A. in A.I. News Reporting: A Comparative Analysis of the Washington Post and South China Morning Post. Issue 1 (March 2022) - Nguyen, Dennis; Hekman, Erik
This study explores the news framing of A.I., China, and the U.S.A. in two mainstream news outlets: The Washington Post and The South China Morning Post . The main objective is to analyse how both, as parts of different discourse cultures, portray the competition for leadership in A.I. innovation between China and the U.S.A. The study takes a critical look at the media discourse on the 'new arms race' and what role the news play in localising global technology trends. The empirical part makes use of a combination of manual and automated content analyses. To this end, a dictionary approach that utilises Names Entity Recognition was applied to a large volume of news texts ( N = 3.055) to identify recurring news frames. The findings show similarities in the perception of A.I.'s potentials and versatility but also clear cultural differences in how risks and conflicts are portrayed in both outlets. Although the Washington Post appears more critical about A.I., the South China Morning Post frames the technology as a driver of economic growth and global influence. The discussion offers a starting point for theorising the relationship between mediatisation, tech trends, cultural differences, and international politics.